Corto animato, l’aporia di un adattamento in fuga=Animated Corto, the aporia of a runaway adatptation - Luca Bandirali (H-ermes: Journal of Communication, 2015)
Animated Corto, the aporia of a runaway adatptation. Although Hugo Pratt was inspired by a movie (Byron Haskin’s His Majesty O’Keefe, starring Burt Lancaster) while creating his main character Corto Maltese, he later became a life-long enemy of his character’s screen adaptation, as he rejected several attemps by either american or european studios. After Pratt’s death in 1995, french Canal+ and italian Rai Fiction started a medium-high budget production based on Corto Maltese’s long stories, including a collection of the short ones. The essay deals with the comic book adaptation theories and examines the main adaptations of Corto Maltese stories, focusing on the aporia of fidelity in the field of intersemiotic translation.